Bibliographic Ghostbusting: The Evanescent Life and Spirited Times of the Canadian Journal of Homoeopathy (1856-57) - Connor, J. T. H. (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2021)
Until recently, analysis of the Canadian Journal of Homoeopathy proved to be difficult; the possibility that this periodical was a bibliographic ghost was plausible. This discussion is based on a close reading of the publication, however, now that a complete run of it is readily and conveniently accessible. This account examines the social and intellectual contexts and also the content of this periodical devoted to mid-Victorian medical reform, in particular the medical sectarian practice of homeopathy in Canada West (previously identified as Upper Canada then later as Ontario), while situating its production and publication within other studies of print culture and medical journalism in Canada. Pivotal in this enterprise as founding editor and publisher were the efforts of homeopath Dr. W.A. Greenleaf of St. Catharines and Hamilton.